PROTECTION OF JOBSEEKERS PARTICIPATING IN JOB ANNOUNCEMENTS AND ADVERTISEMENTS, AND THE RIGHT TO AN EFFECTIVE REMEDY IN THE GENERAL EMPLOYMENT REGIME - Kovačević, Ljubinka (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Public job announcements and advertisements are instruments through which the constitutional principle that all available jobs must be accessible to everyone under equal conditions can be realized.  The application of this principle is most closely connected with the effective exercise of freedom of work and the right to work, which is why the procedure of recruitment cannot be beyond the scope of control which enables immediate elimination of irregularities in this procedure. In that sense, this article discusses the issue of the right of participants in public announcements or job advertisements to an effective remedy, not only via the right to judicial and extrajudicial remedies, but also via the right to object or appeal, as the means to achieve internal protection of rights. This issue is especially delicate in the Republic of Serbia because the Labour Act does not recognize the two-instance internal procedure, while judicial protection of the rights of jobseekers hasn’t been directly regulated, with the exception of protection against discrimination, as well as protection of workers whose employment was previously terminated due to redundancy, resulting in their employment priority when hiring for the same jobs. This solution is accompanied by a number of open questions, especially as the participants in public announcements and job advertisements procedures in special employment regimes in the same situation enjoy the two instance internal protection, which calls into question the effective application of the principle of equality before the law. The article therefore formulates proposals de lege ferenda to create conditions for effective exercise of the right to work, freedom of work and protection against discrimination in a procedure in which a worker will seek to acquire a status that will provide him with the means of subsistence as well as an opportunity to develop his personality through work.
Keywords: right to work; freedom of work; entering into employment relationship; job advertisements; right to an effective remedy; two-instance protection of labour rights; judicial protection of labour rights